Laparoscopic cholecystectomy under local anesthesia and sedation - سليمان جمال (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Laparoscopic cholecystectomy has become the first internationally used treatment option for the treatment of many lesions that affect the gallbladder, including gallstones and polyps. The surgery is usually performed under general anesthesia, but in some cases general anesthesia may be difficult or not possible, which precludes the possibility of the procedure. Objective: the possibility of performing laparoscopic cholecystectomy under local anesthesia and sedation when general anesthesia is not available, or when it is difficult to perform it for patients who suffer from intubation difficulties or want to perform surgery under local anesthesia because of their fear of general anesthesia. Materials and methods : A prospective study was conducted that included 30 patients who attended the General Surgery Department at Tishreen University Hospital during the year 2021 with a history of biliary lesions that require cholecystectomy. The surgery was performed under local anesthesia and sedation using ketofol (2 ml ketamine + 10 ml propofol). Results: The study sample included 30 patients who underwent cholecystectomy under local anesthesia and sedation, 24 patients out of 30 patients (study sample) completed the surgical work without any problems and were completely satisfied with the surgical work, 3 patients out of 30 patients (study sample) needed To administer 1 ml of Atracurium (a muscle relaxant) as a result of severe spasm of the abdominal wall, 3 patients out of 30 patients (the study sample) failed to complete the surgical procedure. They were under local anesthesia and sedation, and they were transferred to general anesthesia as a result of the peritoneal pain resulting from the irritation of the peritoneum with gas. Conclusions: Laparoscopic cholecystectomy under local anaesthesia and sedation is considered a reasonable treatment option as an alternative to the procedure under general anaesthesia if it cannot be performed under general anaesthesia.